2008
DOI: 10.1007/s11661-008-9534-1
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Secondary Reaction Zones in Diffusion Aluminide-Coated Ni-Base Single-Crystal Superalloys Containing Ruthenium

Abstract: The formation of secondary reaction zones (SRZs) beneath aluminide coatings in several Ru-bearing single-crystal Ni-base superalloys has been investigated. The presence of significant amounts of Ru in the superalloys did not prevent the formation of the secondary reaction zone. However, the Ru content of the alloys affected the type of refractory element-rich phase formed during the transformation. As the Ru content increased, the phase involved in the transformation shifted from the orthorhombic P to the b-Ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…Similar results were found in a MCrAlY coated Co-based superalloy [47]. Das et al [42] pointed out that no SRZ formed in the SC superalloys coated by Pt-Hf modified ␥-␥ coatings. In this work, however, SRZ in the NiCrAlY coated specimens was observed too.…”
Section: Inter-diffusion Between the Coatings And The Sc Superalloy Ssupporting
confidence: 68%
See 2 more Smart Citations
“…Similar results were found in a MCrAlY coated Co-based superalloy [47]. Das et al [42] pointed out that no SRZ formed in the SC superalloys coated by Pt-Hf modified ␥-␥ coatings. In this work, however, SRZ in the NiCrAlY coated specimens was observed too.…”
Section: Inter-diffusion Between the Coatings And The Sc Superalloy Ssupporting
confidence: 68%
“…2d). It is well known that the solidsolubility of refractory elements such as Cr, W, Mo and Re in ␥-Ni are much higher than that in ␤-NiAl and ␥ -Ni 3 Al [42]. So, when the ␥-Ni phases transform into ␤-NiAl as a result of inward diffusion of Al, the refractory elements will precipitate out and aggregate into particles.…”
Section: Inter-diffusion Between the Coatings And The Sc Superalloy Smentioning
confidence: 99%
See 1 more Smart Citation
“…Since the SRZ formation can destroy the and 0 coherent two-phase microstructure, which accordingly leads to a deterioration of mechanical properties of the substrate, understanding of formation kinetics of SRZ is important. [5][6][7][8] On the other hand, microstructural anisotropy of Ni-based superalloys which were fabricated by the directionally solidified method can cause anisotropic microstructural differences. There is another important report which revealed that surface re-crystallization formed during service at elevated temperatures was promoted by the residual stress that had been applied to the components during machining.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar fashion, enhanced microstructural coarsening will take place when a coarse microstructure is in contact with a fine one. Typical examples include the development of precipitate-free zones and secondary reaction zones, as well as the formation of new phases [16][17][18][19][20]. Of scientific interest and technical importance is the fact that the new microstructures formed in the interdiffusion or reaction zones are significantly different from the starting microstructures of the individual alloys.…”
Section: Introductionmentioning
confidence: 99%